2014
DOI: 10.4253/wjge.v6.i7.266
|View full text |Cite
|
Sign up to set email alerts
|

Management of early asymptomatic gastrointestinal stromal tumors of the stomach

Abstract: Gastrointestinal stromal tumors (GIST) are the most common mesenchymal tumors of the digestive tract. Approximately two thirds of clinically manifest tumors occur in the stomach, nearly one third in the small bowel, and the rest in the colorectal region with a few cases in the esophagus. GIST originate within the smooth muscle layer in the wall of the tubular gastrointestinal tract and grow mostly toward the serosa, far less often toward the mucosa. In the latter case, ulceration may develop and can cause gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 33 publications
1
45
0
1
Order By: Relevance
“…The MIB-1 labeling index was <1%. These features were compatible with those of low-risk GIST [8, 9, 10]. …”
Section: Case Reportsupporting
confidence: 68%
“…The MIB-1 labeling index was <1%. These features were compatible with those of low-risk GIST [8, 9, 10]. …”
Section: Case Reportsupporting
confidence: 68%
“…5,6 Given their small size, patients are often asymptomatic and tumors are typically discovered incidentally during endoscopic procedures by gastroenterologists or during cross-sectional radiologic studies. 710 It has been reported that up to 30 % of people have small GIST. 1114 However, this data comes from autopsy studies and retrospective pathological series, making it limited by several biases.…”
Section: Introductionmentioning
confidence: 99%
“…GISTs account for about 80% of gastrointestinal sarcomas, with a mean annual incidence of 10-15 per million [4, 5]. Nearly 50-70% of the clinically apparent tumors arise in the stomach, 20-30% arise in the small intestine, 5-15% in the large intestine, and less than 5% in other locations [6]. Activating mutations in the c- KIT (the normal cellular homologue of the Hardy Zuckerman 4 feline sarcoma viral oncogene homologue, NCBI gene ID: 3815) or the platelet-derived growth factor α ( PDGFRA ) proto-oncogenes exist in about 85% of GISTs and are important factors in the pathogenesis of these tumors [7, 8].…”
Section: Introductionmentioning
confidence: 99%